2012
DOI: 10.1016/j.compmedimag.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

MDCT quantification is the dominant parameter in decision-making regarding chest tube drainage for stable patients with traumatic pneumothorax

Abstract: It is commonly believed that the size of a pneumothorax is an important determinant of treatment decision, in particular regarding whether chest tube drainage (CTD) is required. However, the volumetric quantification of pneumothoraces has not routinely been performed in clinics. In this paper, we introduced an automated computer-aided volumetry (CAV) scheme for quantification of volume of pneumothoraces in chest multi-detect CT (MDCT) images. Moreover, we investigated the impact of accurate volume of pneumotho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
13
0
3
Order By: Relevance
“…In these patients, pneumothorax might not have been diagnosed if CT had not been performed, persisting as occult pneumothorax instead. (16,17) In all, 19 (63.3%) out of 30 patients were treated conservatively without chest tube insertion in our study. Other studies have reported that 48% of patients with occult pneumothorax were treated conservatively.…”
Section: Discussionmentioning
confidence: 72%
“…In these patients, pneumothorax might not have been diagnosed if CT had not been performed, persisting as occult pneumothorax instead. (16,17) In all, 19 (63.3%) out of 30 patients were treated conservatively without chest tube insertion in our study. Other studies have reported that 48% of patients with occult pneumothorax were treated conservatively.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, tube thoracostomy may bring along complications such as nonfunctioning or malposition of chest tube, wound infection, abdominal or thoracic injury and vascular trauma in 2-10% of the patients [4][5][6]. Advantages of minimally invasive surgery offered by VATS have oriented many institutions to accept this method as the preferred treatment for patients with chest trauma [14].…”
Section: Resultsmentioning
confidence: 99%
“…However, the optimal management for stable patients continues to be debated considering that complication and failure of inapropriate interventions may rate up to 30% [6].…”
mentioning
confidence: 99%
“…Next to clinical symptoms, the treatment decision can be partially supported by the pneumothorax extent or volume as measured on chest radiographs or computed tomography (CT) scans [4][5][6]. When the cause is spontaneous, a 'large' pneumothorax is defined as larger than 3 cm or than 15% of the volume of the hemithorax and requires aspiration [7].…”
Section: Introductionmentioning
confidence: 99%